Haunted prisons - Williams, Dinah (New York, N.Y. : Bearport Pub., 2014)
Explores the history of eleven haunted prisons, most of them located in the United States.
Haunted prisons -- Death on the Rock -- A place worse than war -- A dangerous hostess -- Ghost of a gangster -- Last man hanging -- Firing squad hero -- The death house -- A headless queen -- Dead but not gone -- The black dog of Newgate -- The warden and his wife -- Haunted prisons around the world.
Includes bibliographical references (p. 31) and index.
5.8
5-8
Keywords: Haunted prisons -- Juvenile literature; Ghosts -- Juvenile literature; Haunted prisons; Ghosts; Haunted prisons; Ghosts; Haunted places; Ghosts